The brain in three crustaceans from cavernous darkness - Stegner, Martin EJ (BMC Neurosci, 2015)
BACKGROUND: While a number of neuroanatomical studies in other malacostracan taxa have recently contributed to the reconstruction of the malacostracan ground pattern, little is known about the nervous system in the three enigmatic blind groups of peracarids from relict habitats, Thermosbaenacea, Spelaeogriphacea, and Mictocarididae. This first detailed description of the brain in a representative of each taxon is largely based on a combination of serial semi-thin sectioning and computer-aided 3D-reconstructions. In addition, the mictocaridid Mictocaris halope was studied with a combination of immunolabeling (tubulin, nuclear counter-stains) and confocal laser scanning microscopy, addressing also the ventral nerve cord. RESULTS: Adjacent to the terminal medulla, all three representatives exhibit a distal protocerebral neuropil, which is reminiscent of the lobula in other Malacostraca, but also allows for an alternative interpretation in M. halope and the thermosbaenacean Tethysbaena argentarii. A central complex occurs in all three taxa, most distinctively in the spelaeogriphacean Spelaeogriphus lepidops. The deutocerebral olfactory lobe in M. halope and S. lepidops is large. The comparably smaller olfactory lobe in T. argentarii appears to be associated with a unique additional deutocerebral neuropil. A small hemiellipsoid body exists only in the protocerebrum of T. argentarii. Distinctive mechanosensory neuropils corresponding to other malacostracans are missing. CONCLUSIONS: The considerable reduction of the optic lobe in the studied taxa is higher than in any other blind malacostracan. The large size of deutocerebral olfactory centers implies an important role of the olfactory sense. The presence of a distinctive central complex in the blind S. lepidops adds further support to a central-coordinating over a visual function of this structure. The lack of a hemiellipsoid body in M. halope and S. lepidops suggests that their terminal medulla takes over the function of a second order olfactory center completely, as in some other peracarids. The reduction of the optic lobe and hemiellipsoid body is suggested to have occurred several times independently within Peracarida. The missing optic sense in the studied taxa is not correlated with an emphasized mechanosense.